Measuring poverty in Britain as a multi-dimensional concept, 1991 to 2003 - Tomlinson, M (2008)
This is a technical appendix for a paper to be published in the Journal of Social Policy. It is reproduced here for interested parties. Paper reference: 'Measuring Poverty in Britain as a Multi-dimensional Concept, 1991 to 2003' Mark Tomlinson, Robert Walker, Glenn Williams Journal of Social Policy, 2008 (forthcoming) Not originally intended for publication, but shows the more detailed path diagrams and detailed results from the two CFA models in the paper.